Industrialization of knowledge in the University of Miskolc - Helmeczi, Ágnes; Darabos, Éva (International Journal of Engineering and Management Sciences, 2019)
Life of universities has transformed thanks to “massification”. The costs of education have increased and universities had to manage a higher number of people. The economic management has moved towards business-like operation. The university has been transformed into an entrepreneurial university, while science has become knowledge production. The scientific policy has started to serve the needs of industrial corporations. The article titled (Industrialization of knowledge) introduces the research, developments, and innovations of the University of Miskolc. The university participate in national and international projects and they use the benefits of the research in developments. As the participants of innovations, they help in the introduction of new technical developments and the preparation of new products. Their operational experience is important for everybody.